The relationship between rotator cuff integrity and acromiohumeral distance following open and arthroscopic rotator cuff repair - Kholinne, Erica (SICOT J, 2021)
Background: Acromiohumeral distance (AHD) has become both a diagnostic and prognostic parameter related to rotator cuff pathology which is always measured in a 2-dimensional plane. The purposes of this study were (1) to evaluate the regional AHD with MRI following open and arthroscopic rotator cuff repair and, (2) to investigate its association to the rotator cuff integrity following medium to large size rotator cuff repair with open and arthroscopic manner. Methods: A retrospective review of 112 patients who were treated for full-thickness medium to large size rotator cuff tears either by open repair (open group) or arthroscopic repair (arthroscopic group) was done. All patients included in the study are those with at least 12 and 18 months for the post-operative MRI and clinical follow-up. Propensity score matching was used to select controls matched for age, sex, body mass index, tear size, and affected site. There were 56 patients in each group with a mean age of 63.3 years (range, 50 to 77 years). The post-operative functional and radiologic outcomes for both groups were compared. AHD was measured at three regions of interest (ROI) with MRI and compared pre-and post-operatively. Results: AHD was significantly greater in the open group when measured at the anterior third of the lateral acromion border compare to the arthroscopic group (p = 0.005). The re-tear rate was affected by AHD at the anterior third of the lateral border of the acromion for the arthroscopic and open group (p = 0.021, p = 0.029). The AHD measured at the anterior and middle third of lateral acromion border were significantly greater in healed compared to the re-tear rotator cuff group (p = 0.019, p = 0.022). Conclusions: Open rotator cuff repair showed greater AHD at the anterior third of the lateral border of the acromion. Regional AHD measured at anterior third of the lateral border of acromion significantly associated with rotator cuff integrity following repair. Level of evidence: propensity-matched case-control (Level II)